Anisotropic Etching of Graphite Flakes with Water Vapor to Produce Armchair‐Edged Graphene. Issue 14 (26th March 2014) - Luo, Da; Yang, Feng; Wang, Xiao; Sun, Hao; Gao, Dongliang; Li, Ruoming; Yang, Juan; Li, Yan
<x xml:space="preserve">Abstract</x> A one‐step anisotropic etching method is developed to specifically obtain armchair‐edged graphene directly from graphite flakes on various substrates. The armchair edge structure of the produced graphene is verified by the atomic resolution images obtained from the fluid mode peakforce tapping AFM and the relatively high intensity of D band in the Raman spectra. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>